Lead poisoning influences TCR-related gene expression patterns in peripheral blood T-lymphocytes of exposed workers. (January 2015) - Niu, Yuzhe; Yu, Wei; Fang, Su; Liu, Sichu; Yang, Zhiqian; Liu, Weiwei; Chen, Shaohua; Yang, Lijian; Li, Bo; Li, Yangqiu
Abstract Previous studies have shown that occupational lead (Pb) exposure might influence human T-lymphocyte function, including such as changes in T-cell receptor (TCR) Vβ and Vγ repertoire and in expression of the TCRζ gene. Thus, the study here further investigated expression of TCRζ-related factors and the FcεRIγ gene (whose product has a functional role complementary to the TCRζ chain) and the Elf-1 gene whose product is involved in regulation of TCR expression. Quantitative real-time RT-PCR was used to measure expression of TCRζ, FcεRIγ, and Elf-1 genes in peripheral blood mononuclear cells (PBMC) isolated from 17 Pb-exposed workers. Samples were collected before and after the workers had undergone chelation therapy regimens. Twenty-three healthy individuals served as controls. The results showed that TCRζ, FcεRIγ, and Elf-1 gene expression in Pb-exposed workers before chelation therapy was significantly lower than in PBMC from healthy individuals. After chelation therapy, expression of TCRζ appeared to trend toward normal levels; in comparison, lower expressions of FcεRIγ and Elf-1 persisted. In conclusion, the previously-documented impairment of T-lymphocyte functions and T- lymphocyte-mediated immune responses seen previously in response to occupational Pb exposure might be attributable, in part, to effects on TCR signaling pathways - including those related to TCRζ and FcεRIγ - and to any down-regulation of membrane TCRζ expression/activity that might be associated with Pb-induced effects on Elf-1 expression.